2011
DOI: 10.1016/j.yhbeh.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ovariectomy on binge eating proneness in adult female rats

Abstract: Ovarian hormones are associated with binge eating in women, however findings are limited by the lack of experimental control inherent in human studies. Animal research that manipulates ovarian hormone status and examines individual differences in extreme binge eating proneness are needed to model clinical phenotypes in humans and to confirm causal effects. The purpose of this study was to examine the effects of adult ovariectomy on overall binge eating risk and extreme binge eating phenotypes using the binge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 45 publications
8
58
1
Order By: Relevance
“…This observation is in line with earlier reports that OVX rats show potentiated binge-like eating compared with gonad-intact female rats (12), while replacement with 17β-estradiol and progesterone suppresses binge-like eating in female OVX rats (13). Here, we further pinpointed that estrogen replacement alone can efficiently suppress bingelike eating behavior in female mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in line with earlier reports that OVX rats show potentiated binge-like eating compared with gonad-intact female rats (12), while replacement with 17β-estradiol and progesterone suppresses binge-like eating in female OVX rats (13). Here, we further pinpointed that estrogen replacement alone can efficiently suppress bingelike eating behavior in female mice.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, circulating 17β-estradiol levels are inversely associated with binge eating in women (7)(8)(9)(10)(11). Consistently, removal of endogenous ovarian hormones by ovariectomy (OVX) potentiates binge eating in female rats (12), whilereplacement with 17β-estradiol and progesterone in OVX rats suppresses binge eating (13). While these data suggest that hormone replacement therapy could be used to suppress binge-like eating, at least in women, the clinical application of ovarian hormones, e.g., estrogens, is limited by their gynecological and tumor-promoting actions.…”
Section: Introductionmentioning
confidence: 90%
“…In another study (393), they detected significant heritability for disordered eating in 10 -15-yr-old girls with higher plasma estradiol levels, but not in girls with lower estradiol levels. Pursuing these effects in a rat model, they found that a binge-eating trait emerged in vulnerable rats during puberty (398), but that ovariectomizing these rats increased binge size rather than eliminating binges (397). Taken together, these data suggest that 1) an organizational effect of estrogens at puberty acts on a genetically determined vulnerability to facilitate the development of bingeing in girls and 2) an activational effect of estrogens thereafter may limit binging (please see Ref.…”
Section: R1245 Sex Differences In the Physiology Of Eatingmentioning
confidence: 96%
“…Specifically, removal of the source of ovarian hormones through bilateral ovariectomy in rats causes increased food intake, and adminstration of estradiol reverses this effect. In contrast, progesterone causes increased food intake, in part, by antagonizing the inhibitory effects of estradiol (68). …”
mentioning
confidence: 99%